From resolving land disputes to agrarian justice – dealing with the structural crisis of plantation agriculture in eastern DR Congo. Issue 2 (23rd February 2022) - van Leeuwen, Mathijs; Mathys, Gillian; de Vries, Lotje; van der Haar, Gemma
ABSTRACT: Land disputes in conflict-affected settings are often considered as a security threat, to be addressed through mediation and strengthening the rule of law. This overlooks the roots of land conflicts in longer-term processes of agrarian development and worsening conditions of land and labour access. A case-study of a dispute between former plantation labourers and concession holders in eastern DR Congo shows mediation's incapacity to counter perceived structural injustices in land access and difficulties in making a living. While dispute resolution may temporarily calm down tensions, it cannot substitute for fundamental political choices vis-a-vis wider questions of agrarian development and justice.